2000
DOI: 10.2134/jeq2000.00472425002900010017x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Management at the Watershed Scale: A Modification of the Phosphorus Index

Abstract: We considered hydrologic and chemical factors controlling P export from a 39.5-ha mixed land use watershed in east-central Pennsylvania, focusing our evaluation on watershed vulnerability to P loss. The spatial variations of P source factors, soil P, and P inputs from fertilizer and manure were evaluated. Distribution of Mehlich-3 soil P on a 30-m grid over the watershed showed that soil P varied with land use. Soils in wooded areas had low Mehlich-3 P (<30 mg kg" 1); grazed pasture had Mehlich-3 P values betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
194
0
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(207 citation statements)
references
References 0 publications
0
194
0
11
Order By: Relevance
“…Damage caused by treading (Elliott et al 2002), decreased soil organic matter (Naeth et al 1991b;Betteridge et al 1999), and reduced leaf litter results in a reduction of aboveground water-holding capacity of the soil (Naeth et al 1991a), decreasing infiltration rate and increasing the volume of surface runoff. Management practices that reduce the total volume of surface runoff and encourage infiltration will reduce the potential for sediment and P losses from pastures (Gburek et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Damage caused by treading (Elliott et al 2002), decreased soil organic matter (Naeth et al 1991b;Betteridge et al 1999), and reduced leaf litter results in a reduction of aboveground water-holding capacity of the soil (Naeth et al 1991a), decreasing infiltration rate and increasing the volume of surface runoff. Management practices that reduce the total volume of surface runoff and encourage infiltration will reduce the potential for sediment and P losses from pastures (Gburek et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Source factors are important in order to estimate nutrient availability such as P availability, yet delivery of P is conditioned by transport factors [27]. In fact, "transport factors are what transform potential P sources into actual P losses from a field or watershed" [33]. Hence, a risk assessment method is selected in this study in order to determine the potential for P loss from livestock farms in a non NVZ.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…In this regard, steep slope and short distance of these intermediate sources to watercourses significantly increase the risk of nutrients loss [33]. Furthermore, it should be pointed out that Farm 4 received in 2009 a report from the ECSFDI where several recommendations were made in order to prevent polluted water from entering the nearby stream.…”
Section: Transport Managementmentioning
confidence: 99%
“…The use of P from mineral fertilizers was always important for plant production, but in the last decade it became a source of potential risk to environmental contamination [50,51]. Although excessive phosphorus accumulation in the soil may have a negative influence on environment, leading to eutrophication [52][53][54][55][56], it should be noted that the relation between the phosphorus content in the soils and its leaching dynamics are still not yet understood. Sharpley [57] showed that the amount of P leached to surface waters is the function of plant growth system and of soil quality.…”
Section: Nitrogen and Phosphorus Use Efficiencymentioning
confidence: 99%